Laboratory Core-flooding Test of Surfactant-Polymer Injection Method for Oilfield Production Improvement - Dedy Kristanto; Wibowo Wibowo; Hariyadi Hariyadi; Yulius Deddy Hermawan (Eksergi, 2019)
The utilization of chemical flooding to improve oil production in a large scale has many used for the oil field. Some cases have a success, and the others have fail when full scale project implemented. Before chemical flooding conducted, once of the recommended best practice to be done is chemical compatibility based on the reservoir characteristic of the layer as a target in improving oil recovery. Hence, coreflooding test in the laboratory to be an important thing to conduct in other to knows and determine the chemical performance after screening phase. The study of coreflooding test in the laboratory, shows that the measurement of surfactant and polymer properties have a good results to be used as an injection fluid in other to improve oil production. Surfactant - polymer injection which has concentrations of 3000 ppm and 1000 ppm with injection mechanism of 0.3 PV surfactant and 0.2 PV polymer gives the result of improving oil production it about 12.89%. Furthermore, based on the qualitative analysis obtained that the used of surfactant SS-B8020 as an injection fluid shown that plugging has not occurred in the reservoir rock pores, it means that the injection fluid was compatible with these reservoir rock.